EXECUTIVE COMPENSATION AND FINANCIAL REPORTING QUALITY OF NIGERIAN FINANCIAL SERVICE INDUSTRY - T., Adeoye Ebunoluwa; O., Akinkoye Ebenezer; Tajudeen, Ayoola; Godwin, Inneh; I., Agelebe Glory (International Journal of Accounting & Finance Review, 2021)
The study evaluated the effect of executive compensation on financial reporting quality in Nigerian financial service industry for the period covered. These were with a view to providing information on the effect of executive compensation and financial reporting quality in Nigeria. The study employed a secondary source of data collection. The population for the study consisted of 22 quoted deposit money banks listed and whose stocks are actively traded on the Nigerian Stock Exchange (NSE) market for the period 2006-2017.The sample size of 14 was determined using purposive sampling method. Secondary data were collected on variables executive compensation, non-performing loan, loan loss provision, total loan, residual term all obtained from the audited Annual reports of the selected deposit money banks, fact book published by Nigerian Stock Exchange, and the Central Bank of Nigeria. Data collected were analyzed using Robust Regression. The results showed executive compensation (coef. =-0.139, p˂0.004) has a negative significant relationship with financial reporting quality. This study concluded that executive compensation has a negative significant effect on financial reporting quality.